2015
DOI: 10.1038/jhg.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Older individuals heterozygous for a growth hormone-releasing hormone receptor gene mutation are shorter than normal subjects

Abstract: Growth hormone (GH)-releasing hormone (GHRH) is the most important stimulus for GH secretion by the pituitary gland. Subjects homozygous for GHRH receptor (GHRHR) gene (GHRHR) inactivating mutations have severe GH deficiency, resulting in severe short stature if not treated. We previously reported that young adults heterozygous for the c.57+1G>A null GHRHR mutation (MUT/N) have reduced weight and body mass index (BMI) but normal stature. Here we have studied whether older MUT/N have an additional phenotype. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…308 Several studies inferred that the GHRHR SNPs rs17159772, rs4988494, rs2267721, rs4988498, and rs4988505 were associated with reduced human height, indicating that GHRHR might affect normal human height variation. 309312 Furthermore, the phenotype of pituitary dwarfism was also observed in individuals with GHRHR mutations (IVS1 + 1G→A or IVS8+1G>A). 313318 Harsloef et al and Torekov and colleagues reported that the GIPR polymorphism Glu354Gln (rs1800437) was associated with reduced human BMD and bone mass and increased fracture risk.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 96%
“…308 Several studies inferred that the GHRHR SNPs rs17159772, rs4988494, rs2267721, rs4988498, and rs4988505 were associated with reduced human height, indicating that GHRHR might affect normal human height variation. 309312 Furthermore, the phenotype of pituitary dwarfism was also observed in individuals with GHRHR mutations (IVS1 + 1G→A or IVS8+1G>A). 313318 Harsloef et al and Torekov and colleagues reported that the GIPR polymorphism Glu354Gln (rs1800437) was associated with reduced human BMD and bone mass and increased fracture risk.…”
Section: Diseases or Dysfunction Caused By Gpcr Mutation Or Deletion mentioning
confidence: 96%
“…In contrast, older HTZ individuals are in average 4.2 cm shorter than controls, showing ageassociated height reduction, possibly suggesting frailty, a public health problem. These data indicate different effects of heterozygosis through lifespan (80). Table 1 summarizes the principal findings in this IGHD group.…”
Section: Heterozygous (Htz) Phenotypementioning
confidence: 96%
“…These features have been published in 42 different publications (2,19,22,25,27,29,30,31,32,33,36,37,38,40,41,44,45,46,47,48,49,50,51,52,53,54,56,57,61,62,63,64,66,67,68,74,75,76,77,78,79,80). We have used this experiment of nature to discover 'usual laws of nature' as suggested by William Harvey, and to understand some aspects of more common conditions such as short stature, insulin resistance, diabetes, atherosclerosis, osteoporosis, cancer and ultimately longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Of these neighbors, two or three were sorted and contacted. If they fit the eligibility criteria, presenting normal homozygous wild‐type GHRHR allele according with our data banking with genotyped individuals from this community, and matched characteristics (age, sex, socioeconomic condition assessed by monthly income, diabetes, and smoking status), they were invited to participate in the study as a control group. All participants were informed of the nature and potential risks of their participation, and all signed a term of informed consent.…”
Section: Methodsmentioning
confidence: 99%